Involvement of GATOR complex genes in familial focal epilepsies and focal cortical dysplasia. (13th May 2016) - Weckhuysen, Sarah; Marsan, Elise; Lambrecq, Virginie; Marchal, Cécile; Morin‐Brureau, Mélanie; An‐Gourfinkel, Isabelle; Baulac, Michel; Fohlen, Martine; Kallay Zetchi, Christine; Seeck, Margitta; de la Grange, Pierre; Dermaut, Bart; et al.
Summary: Objective: The discovery of mutations in DEPDC5 in familial focal epilepsies has introduced a novel pathomechanism to a field so far dominated by ion channelopathies. DEPDC5 is part of a complex named GAP activity toward RAGs (GATOR) complex 1 (GATOR1), together with the proteins NPRL2 and NPRL3, and acts to inhibit the mechanistic target of rapamycin (mTOR) complex 1 (mTORC1) pathway. GATOR1 is in turn inhibited by the GATOR2 complex. The mTORC1 pathway is a major signaling cascade regulating cell growth, proliferation, and migration. We aimed to study the contribution of GATOR complex genes to the etiology of focal epilepsies and to describe the associated phenotypical spectrum. Methods: We performed targeted sequencing of the genes encoding the components of the GATOR1 (DEPDC5, NPRL2, and NPRL3) and GATOR2 (MIOS, SEC13, SEH1L, WDR24, and WDR59 ) complex in 93 European probands with focal epilepsy with or without focal cortical dysplasia. Phospho‐S6 immunoreactivity was used as evidence of mTORC1 pathway activation in resected brain tissue of patients carrying pathogenic variants. Results: We identified four pathogenic variants in DEPDC5, two in NPRL2, and one in NPRL3 . We showed hyperactivation of the mTORC1 pathway in brain tissue from patients with NPRL2 and NPRL3 mutations. Collectively, inactivating mutations in GATOR1 complex genes explained 11% of cases of focal epilepsy, whereas no pathogenic mutations were found in GATOR2 complex genes. GATOR1‐related focal epilepsies differ clinically from focal epilepsies due to mutations in ion channel genes by their association with focal cortical dysplasia and seizures emerging from variable foci, and might confer an increased risk of sudden unexplained death in epilepsy (SUDEP). Significance: GATOR1 complex gene mutations leading to mTORC1 pathway upregulation is an important cause of focal epilepsy with cortical malformations and represents a potential target for novel therapeutic approaches.